Construction of Streptococcus pyogenes mutants by allele replacement mutagenesis - Shahdan, Intan Azura; Smith, Wendy; Kehoe, Mike (2010)
S. pyogenes secrete a large array of molecules that might contribute to resistance against antimicrobial peptides (AMPs). Some of these are anchored in the cell-wall by enzymes called sortases and others are released from the cell after secretion. One of the released proteins that have previously been reported to inhibit bactericidal effect of the AMPs are streptococcal inhibitor of complement (SIC). SIC has been recognised as a substantial virulence factor in the M1 GAS strain AP1, because Δsic mutant failed to colonise mouse throat (Lukomski et al., 2000). In fact, the colonisation of the SIC-negative strain was significantly impaired during the first four days of post-inoculation, showing that SIC is a crucial virulence factor during the early stages of infection by this strain (Lukomski et al., 2000). Hoe and colleagues then showed that GAS Δsic mutant was easily internalised and killed more effectively by human epithelial cells than the wild-type strain (Hoe et al., 2002). Previous studies used SIC-defective mutants which were constructed by insertion of transposon. The disadvantage of such mutagenesis is that the GAS mutants may have retained an intact copy of the sic gene, which could express some SIC protein. Therefore, the specific objective of the project was to construct a sic deletion mutant of GAS strain SF370 by allele-replacement mutagenesis. The constructed mutant would have a genetically clearly-defined deletion mutant, that completely removed sic gene from the S. pyogenes strain SF370 chromosome, without leaving any foreign sequences (such as an inserted plasmid) behind.